2019
DOI: 10.3390/molecules24112077
|View full text |Cite
|
Sign up to set email alerts
|

Sarconesin II, a New Antimicrobial Peptide Isolated from Sarconesiopsis magellanica Excretions and Secretions

Abstract: Antibiotic resistance is at dangerous levels and increasing worldwide. The search for new antimicrobial drugs to counteract this problem is a priority for health institutions and organizations, both globally and in individual countries. Sarconesiopsis magellanica blowfly larval excretions and secretions (ES) are an important source for isolating antimicrobial peptides (AMPs). This study aims to identify and characterize a new S. magellanica AMP. RP-HPLC was used to fractionate ES, using C18 columns, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 134 publications
0
19
0
2
Order By: Relevance
“…In another analysis, the ability of Mygalin to disrupt the cellular membranes of E. coli was evidenced since the treated bacteria incorporated PI, similar to that visualized with ampicillin. DNA damage has been described in the treatment of bacteria with antibiotics (Kohanski et al, 2010), toxic metals (Espirito Santo et al, 2011) and antimicrobial peptides (Farkas et al, 2017;Diaz-Roa et al, 2019), which led to bacterial death. Inhibition of DNA synthesis was confirmed by light microscopy (Alfred et al, 2013) during the treatment of E. coli with Mygalin and ciprofloxacin, a high bacterial stress-inducing antibiotic (Goswami et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In another analysis, the ability of Mygalin to disrupt the cellular membranes of E. coli was evidenced since the treated bacteria incorporated PI, similar to that visualized with ampicillin. DNA damage has been described in the treatment of bacteria with antibiotics (Kohanski et al, 2010), toxic metals (Espirito Santo et al, 2011) and antimicrobial peptides (Farkas et al, 2017;Diaz-Roa et al, 2019), which led to bacterial death. Inhibition of DNA synthesis was confirmed by light microscopy (Alfred et al, 2013) during the treatment of E. coli with Mygalin and ciprofloxacin, a high bacterial stress-inducing antibiotic (Goswami et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum signal required for selecting an ion for a fragmentation event (MS2) was set at 5,000 cps. (8,9) Bioinformatics analysis -MS/MS spectra were selected from a database constructed from the Lucilia UniProt protein databank (17) and the National Centre for Biotechnology Information (NCBI) GenBank database (18) for determining the amino acid (aa) sequences; Proteome Discoverer 1.4 software (Thermo Fisher Scientific Inc) was used as search machine for protein identification. The ProtParam (Expasy) tool was used for calculating the physicochemical parameters, (19) is provided as a service to the life science community by a multidis- ciplinary team at the Swiss Institute of Bioinformatics (SIB ClustalW 2.0 for aligning the sequences (20) and the PEP-FOLD3 server for predicting tertiary structure.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have shown that S. magellanica-derived larval ES have proved effective in treating diabetic rabbits' wounds and as potential therapy against bacterial pathogens. (8,9,15) Such situation becomes even more drastic regarding hard-to-heal wounds in patients having an underlying disease, including diabetes or cardiovascular failure, often involving polymicrobial colonisation by different bacterial strains, such as P. aeruginosa, S. pyogenes, Clostridium perfringens, Corynebacterium spp., Propionibacterium spp., S. aureus and methicillin-resistant S. aureus (MRSA), or in patients in intensive care units (ICU) who have developed a health-care associated-infection (HAI). (16) These ideas have been addressed regarding the detection of new biological properties in S. magellanica-derived AMPs.…”
mentioning
confidence: 99%
“…Antimicrobial peptides and proteins show a wide distribution and have been isolated from nearly all living organisms. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Beyond their antimicrobial effects, several AMPs have been shown to have other biological activities. 11,[22][23][24][25] One such protein group that represents the duplicity of activities for the same molecules is the tachykinin family.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial peptides and proteins show a wide distribution and have been isolated from nearly all living organisms. 8 - 21 …”
Section: Introductionmentioning
confidence: 99%